Interventions for adolescent depression comorbid with non-suicidal self-injury: a scoping review - Fang, Shihan; Chen, Fazhan; Bian, Jing; Zhang, Lei; Wang, Yanbo (Frontiers in Psychiatry, 2025)
BackgroundAdolescent depression and non-suicidal self-injury (NSSI) represent significant global public health challenges, with high comorbidity rates and multidimensional adverse outcomes. Despite growing evidence on interventions, a comprehensive synthesis of strategies targeting this co-occurrence remains limited.AimThis scoping review systematically maps evidence-based interventions for adolescents with comorbid depression and NSSI, focusing on efficacy, mechanisms, and implementation challenges.MethodsFollowing Arksey and O’Malley’s framework and PRISMA-ScR guidelines, a systematic search of English and Chinese databases (2000–2025) identified 18 studies (13 randomized controlled trials [RCTs], 3 quasi-experimental studies, and 2 other study designs). Data were extracted and synthesized to characterize intervention types, outcomes, and contextual factors.ResultsPsychotherapies, particularly dialectical behavior therapy for Adolescents (DBT-A), demonstrated robust efficacy, reducing NSSI frequency by 50% and relapse rates through enhanced emotion regulation. Family-system approaches (e.g., Satir therapy) improved family cohesion and reduced comorbid behaviors. Pharmacological agents (e.g., Selective Serotonin Reuptake Inhibitors) showed synergistic effects when combined with psychotherapy, while neuromodulation (e.g., Repetitive Transcranial Magnetic Stimulation) normalized neuroinflammatory markers. Innovations like narrative therapy facilitated identity reconstruction by externalizing NSSI as a separate entity from self-concept. Key challenges included cultural adaptability, limited long-term follow-up (≥1 year), and understudied digital intervention roles.ConclusionsIntegrated biological-behavioral interventions, culturally tailored protocols, and family-system strategies are pivotal for managing NSSI-depression comorbidity. Future research should prioritize rigorous RCTs with extended follow-up periods, community-based implementation, and digital mental health solutions to address scalability and sustainability gaps.